1979
DOI: 10.1093/schbul/5.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Endorphins, Dopamine, and Schizophrenia*

Abstract: The theory that alterations of dopaminergic synaptic transmission may play a role in the pathogenesis of schizophrenia is widely accepted. A more recent theory links the endorphin system to the etiology of schizophrenia. We propose that these two theories may be combined into a single model. Recent neurochemical and pharmacological findings have indicated close functional relationships between the endorphin and dopamine systems. Endorphins modulate dopaminergic synaptic transmission by exerting both presynapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

1980
1980
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(22 citation statements)
references
References 80 publications
0
20
0
2
Order By: Relevance
“…Endogenous opioid system disturbances have been observed in schizophrenia. The excess of endorphins in schizophrenia is one of the postulated hypothesis . In our previous study, we also found about 20% higher BE concentration in patients with schizophrenia than in healthy controls .…”
Section: Introductionmentioning
confidence: 56%
“…Endogenous opioid system disturbances have been observed in schizophrenia. The excess of endorphins in schizophrenia is one of the postulated hypothesis . In our previous study, we also found about 20% higher BE concentration in patients with schizophrenia than in healthy controls .…”
Section: Introductionmentioning
confidence: 56%
“…Opioid peptides modulate dopaminergic synaptic transmission by exerting both presynaptic and postsynaptic effects; this modulation may involve the activity of nucleotide cyclases and protein phosphorylation systems [9]. Thus, dopaminergic neuronal hyperactivity, currently believed to be related to schizophrenia, might be caused by a primary alteration in the endorphin system.…”
Section: Resultsmentioning
confidence: 99%
“…However, no mutations in dopamine receptors have been clearly associated with disease [5,6]. This lack of evidence has directed efforts towards the examination of defects in dopamine metabolism and/or signal transduction within dopamine pathways including the interaction of dopamine with other neurotransmitter systems as neurotrophic factors [7], cytokines [8], and opioid peptides [9].…”
Section: Introductionmentioning
confidence: 99%
“…Opiates levels tend to parallel the severity of psychosis (Terenius et al, 1976;Lindstrom et al, 1978;Rimon et al, 1980;Marchesi et al, 1995), suggesting involvement of this neurochemical effect in schizophrenia neuropathology (Volavka et al, 1979;Schmauss and Emrich, 1985;Nemeroff and Bissette, 1988).…”
Section: Abnormal Opioidergic Function May Impair Liking Processes Inmentioning
confidence: 99%
“…On the basis of the hypothesis that opioidergic mechanisms are involved in the pathophysiology and symptoms of schizophrenia (Volavka et al, 1979;Schmauss and Emrich, 1985;Nemeroff and Bissette, 1988), opioid antagonists were evaluated for potential antipsychotic efficacy in numerous clinical trials (McNicholas and Martin, 1984;Nemeroff and Bissette, 1988;Welch and Thompson, 1994). On the whole, they were safe and well tolerated and resulted in significant improvements of various aspects of schizophrenic symtomatology such as positive and deficit symptoms, polydipsia, alcoholism, and tardive dyskinesia in some (Watson et al, 1978;Lehmann et al, 1979;Berger et al, 1981;Nishikawa et al, 1994a, b;Marchesi et al, 1995;Petrakis et al, 2004;Wonodi et al, 2004), but not all (Volavka et al, 1977;Pickar et al, 1982) participants.…”
Section: Opioid Antagonists May Improve Hedonic Deficits In Patients mentioning
confidence: 99%